Development of a novel peptide to prevent entry of SARS-CoV-2 into lung and olfactory bulb cells of hACE2 expressing mice - Ping Su; Dongxu Zhai; Albert H. C. Wong; Fang Liu (Molecular Brain, 2022)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that has caused a global pandemic Coronavirus Disease 2019 (COVID-19). Currently, there are no effective treatments specifically for COVID-19 infection. The initial step in SARS-CoV-2 infection is attachment to the angiotensin-converting enzyme 2 (ACE2) on the cell surface. We have developed a protein peptide that effectively disrupts the binding between the SARS-CoV-2 spike protein and ACE2. When delivered by nasal spray, our peptide prevents SARS-CoV-2 spike protein from entering lung and olfactory bulb cells of mice expressing human ACE2. Our peptide represents a potential novel treatment and prophylaxis against COVID-19.